A Subnational Analysis of Mortality and Prevalence of COPD in China From 1990 to 2013: Findings From the Global Burden of Disease Study 2013 - Yin, Peng; Wang, Haidong; Vos, Theo; Li, Yichong; Liu, Shiwei; Liu, Yunning; Liu, Jiangmei; Wang, Lijun; Naghavi, Mohsen; Murray, Christopher J L; Zhou, Maigeng (Chest, 2016)
The trends of COPD mortality and prevalence over the past 2 decades across all provinces remain unknown in China. We used data from the Global Burden of Disease Study 2013 (GBD 2013) to estimate the mortality and prevalence of COPD during 1990 to 2013 at a provincial level. Following the general analytic strategy used in GBD 2013, we analyzed the age- sex- and province-specific mortality and prevalence of COPD in China. Levels of and trends in COPD mortality and prevalence were assessed for 33 province-level administrative units during 1990 to 2013. In 2013, there were 910,809 deaths from COPD in China, accounting for 31.1% of the total deaths from COPD in the world. From 1990 to 2013, the age-standardized COPD mortality rate decreased in all provinces, with the highest reduction in Heilongjiang (70.2%) and Jilin (70.0%) and the lowest reduction in Guizhou (26.8%). In 2013, the death rate per 100,000 was highest in Guizhou (196.0) and lowest in Tianjin (34.0) among men and highest in Gansu (141.1) and lowest in Beijing (23.7) among women. The number of COPD cases increased dramatically from 32.4 million in 1990 to 54.8 million in 2013. The age-standardized prevalence rate of COPD remained stable overall and varied little for all provinces. COPD remains a huge health burden in many western provinces in China. The substantial increase in COPD cases represents an ongoing challenge given the rapidly aging Chinese population. A targeted control and prevention strategy should be developed at a provincial level to reduce the burden caused by COPD.